Pengendalian Persediaan Bahan Baku Pisang Menggunakan Metode EOQ dengan Mempertimbangkan Masa Kedaluarsa dan Pemberian Diskon - Airlangga Muhammad Alfaridz; Suseno Suseno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
UMKM XYZ is one of the developing MSMEs in the food sector with the main product of fried bananas. This company still has not made improvements to inventory management on banana raw materials. Banana raw materials often experience excess every week, causing waste. The rest of the banana raw materials are not reused because the bananas will experience spoilage after passing their expiration date. The importance of controlling raw material inventory in the bussines to reduce the total cost of inventory. Optimal inventory management needs to be a concern for UMKM XYZ because it affects the total cost of inventory. The Economic Order Quantity (EOQ) method which considers the expiration period and provides discounts is one way to solve inventory control problems in a business, by determining the quantity of raw materials that must be bought per order and the budget that must be spent to purchase raw materials, with this a company can reduce the cost of storing raw materials. The findings of studies carried out with the EOQ technique, which considers expiration dates and discounts, show the ideal amount for each order, which is 1,572.78 kg. Therefore, the total inventory cost incurred by UMKM XYZ in one year is IDR 663,301,461 and before using the EOQ method, there is a difference in the total inventory cost of (IDR 764,442,000 - IDR 663,301,461) = IDR 101,140,539. Thus, the EOQ method will be more effective for managing raw material inventory in terms of total inventory costs if applied.